Characterization of Polylysine Enriched Self-Adhesive Resin Cements - Zainab M. Mansi; Abdulla MW Al-Shamma (International Journal of Dentistry)
Aim. The aim of this study is to add polylysine (PLS) particles to two different types of self-adhesive resin cement (RelyXU200 and Breeze) and to characterize them before and after PLS incorporation. Materials and Methods. Four PLS concentrations (0.2%, 1%, 2%, and 5%) were selected for incorporation into two self-adhesive resin cements (RelyXU200 and Breeze), thus the groups of this study include one control group and four experimental groups for each cement type. Different characterization tests were performed including Fourier transform infrared spectroscopy (FTIR), degree of conversion (DC), compressive strength (CS), and ISO tests 4049-2019 that include: film thickness, setting time, water sorption (WS), and solubility (SL). The statistical procedure used includes analysis of variance test (ANOVA) and multiple pairwise comparisons Tukey post hoc test which was used for multifactorial analysis. Results. FTIR showed that PLS addition did not change the functional groups’ peaks for either cement type indicating that no chemical reaction with and/or alteration within the cement has occurred. In general, PLS addition increased the water sorption, solubility, and film thickness, it also increased the setting time for Breeze while decreasing it for RelyXU200 and all these parameters were within 4049-2019 ISO Specification. Statistically, PLS addition did not significantly change these properties compared to the control groups except for 5% PLS. Similarly, the degree of conversion and compressive strength was slightly reduced with no significant difference to the control cement groups except for 5% PLS concentration. Conclusions. Newly developed PLS incorporated self-adhesive resin cement exhibited remarkable mechanical and physical properties compared to control self-adhesive resin cement and passed the ISO standardization. PLS-incorporated resin cement with less than 5% have no negative impact on the physical and mechanical properties of the studied cement.